Analysis of the Utilization of Organic Waste into Biogas Alternative - Rahmat, Firdaus Nur; Sudarti, Sudarti; Yushardi, Yushardi (Politeknik Negeri Semarang, 2023)
Abstract”” Waste is the main problem experienced by somepeople in Indonesia. The population is getting higher in the spanof a year. Unable with the presence of waste consisting of varioustypes of waste, this problem can be felt, namely negative impactson the surrounding environment, for example the slumenvironment, becoming a source of disease nests, and being atrigger for global warming caused by waste. This study has theaim of analyzing the use of the type of organic waste used foralternative energy, namely Biogas. In this study, we used aliterature review approach. An approach similar to the one usedhere is used to collect various data from previously conductedresearch on topics related to those being discussed here. Animalwaste, fruit and vegetable waste, and other forms of organicwaste can be converted into biogas faster than inorganic waste.For the production of biogas, mixing vegetables together isbetter than cutting them. Biogas that has been processed can beused as alternative energy that can benefit various sectors. Theuse of organic waste into biogas can reduce the problem of wastein Indonesia.